2021
DOI: 10.47766/itqan.v13i1.96
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Professionalism of Madrasah Teachers Post Covid-19

Abstract: Covid-19 has had a significant impact on the paradigm shift in Madrasah management. Currently, madrasah managers are aware of the importance of technology-based innovation. This study attempts to analyze the madrasah development model. This type of research is qualitative with a descriptive method. Data were collected through in-depth interviews with the Principal, Curriculum Deputy, Teachers, and several students. The results of the study show that madrasah innovations that are based on increasing the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Clinical reasoning is needed in creating skill-based online learning. The focus of learning is to form cognitive skills, procedural or academic skills that can be taught online effectively (Daulay & Ritonga, 2021;Hanushek & Rivkin, 2012). It is to design an effective pattern of online skills training and education the learning process is promoted when learners are involved in solving real-world problems.…”
Section: Learning Model Based On Technical Skillsmentioning
confidence: 99%
“…Clinical reasoning is needed in creating skill-based online learning. The focus of learning is to form cognitive skills, procedural or academic skills that can be taught online effectively (Daulay & Ritonga, 2021;Hanushek & Rivkin, 2012). It is to design an effective pattern of online skills training and education the learning process is promoted when learners are involved in solving real-world problems.…”
Section: Learning Model Based On Technical Skillsmentioning
confidence: 99%
“…With such circumstances, a teacher must be able to master the class and condition students whose attention is starting to split. Teachers should be able to provide a suitable method (Daulay & Ritonga, 2022) for students to make learning not boring but fun. This is a challenge for teachers to understand the study of ontology and epistemology, where does knowledge come from, and how should knowledge be extracted (Salabi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The principal's managerial competence plays an essential role in improving organizational performance because the supervision of the principal will affect educators and education staff in an institution (Ostime, 2019). The success of the principal shows that the principal is described as the center of the leadership of a school who has the authority to determine the direction of the school (Daulay & Ritonga, 2021). It can be concluded that the success of the school is the success of the principal.…”
mentioning
confidence: 99%